Antioxidant activity, nutritional, and phenolic composition of sweet potato leaves as affected by harvesting period - Suárez, Santiago (2020)
In the present study, the nutritional and phenolic composition as well as the antioxidant activity of sweet potato leaves (SPL) harvested in 3 different periods were determined and compared. Furthermore, gray relational analysis was used to compare the comprehensive nutritional value. Results showed SPL HP1 had the highest protein value (30.8 ± 0.4 g/100 g dw), while SPL HP3 had the highest content of vitamin C (104.6 ± 4.9 mg/100 g dw), vitamin E (5.8 ± 0.4 mg/100 g dw), total polyphenol content (9.1 ± 0.3 g/100 g dw), antioxidant activity (DPPH: 7.4 ± 0.1 g VcE/100 g dw; ABTS: 10.6 ± 0.7 g VcE/100 g dw; FRAP: 0.617 ± 0.005 µmol TroloxE/100 g dw), and comprehensive nutritional value (weighted gray relational grade 0.8336). The individual phenolic composition showed the presence of six caffeoylquinic acids, caffeic acid, and two flavonoids (quercetin and isoquercetin), which were significantly different among different harvest periods. In conclusion, HP3 was an optimal period for harvesting SPL